2018
DOI: 10.1007/s12350-017-1102-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic accuracy of myocardial perfusion imaging in octogenarians

Abstract: Use of MPI in octogenarians is associated with similar or better prognostic accuracy than in younger subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…As regards cardiac deaths, a constant and significantly increase from normal, mildly abnormal, and moderately-to-severely abnormal myocardial perfusion during pharmacologic stress (1.9% vs 2.7% vs 7.8%) or exercise stress (0.7% vs 1.0% vs 2.7%) was observed. Similarly, Nudi et al 1 demonstrated that the extent and severity of myocardial ischemia was also paralleled by a worsened cardiovascular outcome but the current study expands it now to octogenarians in a relatively high numbers of 517 individuals. Thus, current 1 and previous MPS studies 2,3,6,7 signify that MPS may indeed be of help in identifying elderly patients, even when exceeding 80 years, at risk for cardiovascular events.…”
mentioning
confidence: 52%
See 4 more Smart Citations
“…As regards cardiac deaths, a constant and significantly increase from normal, mildly abnormal, and moderately-to-severely abnormal myocardial perfusion during pharmacologic stress (1.9% vs 2.7% vs 7.8%) or exercise stress (0.7% vs 1.0% vs 2.7%) was observed. Similarly, Nudi et al 1 demonstrated that the extent and severity of myocardial ischemia was also paralleled by a worsened cardiovascular outcome but the current study expands it now to octogenarians in a relatively high numbers of 517 individuals. Thus, current 1 and previous MPS studies 2,3,6,7 signify that MPS may indeed be of help in identifying elderly patients, even when exceeding 80 years, at risk for cardiovascular events.…”
mentioning
confidence: 52%
“…Similarly, Nudi et al 1 demonstrated that the extent and severity of myocardial ischemia was also paralleled by a worsened cardiovascular outcome but the current study expands it now to octogenarians in a relatively high numbers of 517 individuals. Thus, current 1 and previous MPS studies 2,3,6,7 signify that MPS may indeed be of help in identifying elderly patients, even when exceeding 80 years, at risk for cardiovascular events. In particular, Nudi et al 1 could demonstrate with a propensity-matched analysis that the MPS-related diagnostic and prognostic accuracy was similar or even better in octogenarians than in younger patients.…”
mentioning
confidence: 52%
See 3 more Smart Citations